PENERAPAN MNEMONIK SEBAGAI METODE ALTERNATIF UNTUK MENGHAFAL HURUF IKHFA’ - Miftakhul Rizal M. (STAI Sangatta Kutai Timur, 2022)
Memorizing is the way of the learning process to receive the material that has been learned. There is an important subject at elementary school, it is tajwid. The materials in Tajwid must be memorized by the learner. There are 15 alphabets of ikhfa’ that must be memorized quickly and easily and also have strong memorization if they will be needed soon. Thus, the researcher researched that has titled implementation of mnemonic as an alternative method to memorize ikhfa’ alphabets. The researcher used a qualitative approach. This research has 14 participants then who are called learners. In the mnemonic method, the teacher arranged the words that represent the alphabet of ikhfa’ and then combined them with the picture that has found or searched by the teacher. The learner follows the voice of the teacher three times about arranging the word ikhfa’. The word is Pak Dhodzo Tsadzin teko Shoqo Kutho pakai Jaz, Syafatu dan Dasi. Then, after memorizing and the learner has memorized the sentences, the teacher tested them to write or speak the 15 alphabets of ikhfa’. Based on the researcher’s survey, all learners can mention 15 alphabets of ikhfa’. This research explains that the implemented mnemonic can be used as an alternative method to memorize 15 alphabets of ihkfa’.